Evaluacion del estado nutritivo de hibiscus elatus sw. (Majagua) al final del cultivo en vivero - Cobas Lopez, M.=700 1 Gonzalez Izquierdo, E.; Sotolongo Soospedra, R.; castillo martinez, I.; Garcia Corona, I.; Medina Malagon, M.
(Es, En)
Ilus., 17 ref.
Keywords: HIBISCUS ELATUS; VIVEROS; FISIOLOGIA VEGETAL; SUELO; CUBA; REVISTA FORESTAL BARACOA